2019
DOI: 10.3171/2019.8.focus19546
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preoperative antiplatelet or anticoagulation therapy on hemorrhagic complications in patients with traumatic brain injury undergoing craniotomy or craniectomy

Abstract: OBJECTIVETraumatic brain injury (TBI) is common among the elderly, often treated with antiplatelet (AP) or anticoagulation (AC) therapy, creating new challenges in neurosurgery. In contrast to elective craniotomy, in which AP/AC therapy is mostly discontinued, in TBI usually no delay in treatment can be afforded. The aim of this study was to analyze the effect of AP/AC therapy on postoperative bleeding after craniotomy/craniectomy in TBI. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 31 publications
4
26
0
Order By: Relevance
“…Hanalioglu et al (2020) studied 1,346 cases of intracranial tumor surgery and reported that discontinued APT before surgery and continued APT during perioperative period all did not significantly increase the probability of postoperative rehematoma. The same conclusion was also obtained in patients with traumatic brain injury undergoing craniotomy or craniectomy (Greuter et al, 2019). Although there were reports that preoperative APT was an independent risk factor for postoperative rehematoma in patients with ICH, the population of this study excluded deep ICH, which was the majority part of ICH (Biffi et al, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…Hanalioglu et al (2020) studied 1,346 cases of intracranial tumor surgery and reported that discontinued APT before surgery and continued APT during perioperative period all did not significantly increase the probability of postoperative rehematoma. The same conclusion was also obtained in patients with traumatic brain injury undergoing craniotomy or craniectomy (Greuter et al, 2019). Although there were reports that preoperative APT was an independent risk factor for postoperative rehematoma in patients with ICH, the population of this study excluded deep ICH, which was the majority part of ICH (Biffi et al, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…2,9,10 Even with an awareness of these adverse events, some factors such as family pressure, medico-legal aspects, and intradepartmental reputation could influence whether an aggressive surgical approach is followed despite the expectation of a poor outcome. 11 Among the outcome predictors, level of consciousness according to the Glasgow Coma Scale (GCS) score, ASDH thickness, and amount of midline shift have been recognized as the most important, 2,6,7,[12][13][14] while the role of antithrombotic therapy 15,16 and the presence of comorbidities 17,18 remain controversial.…”
mentioning
confidence: 99%
“…In the near term, pre-injury anticoagulant or antiplatelet treatment was not associated with acute, postoperative hemorrhage in a retrospective study of 143 neurosurgical (craniotomy and craniectomy) patients. 49 VKA relative to DOAC, antiplatelets or controls has been associated with greater reversal agent use, hematoma expansion and mortality, but unrelated to the need for surgical intervention. 50 Another study demonstrated that DOAC treatment pre-injury was associated with greater likelihood of neurosurgical intervention.…”
Section: Restart Following Surgical Intervention Of Ticrhmentioning
confidence: 99%